5th International Conference on Computer Sciences and Convergence Information Technology 2010
DOI: 10.1109/iccit.2010.5711064
|View full text |Cite
|
Sign up to set email alerts
|

A survey on user involvement in software Development Life Cycle from practitioner's perspectives

Abstract: User involvement is an important issue that is currently discuss in software development industry. This is due to the incidence of user frustration when using a software product. The literature on software development reflected that the involvement of users in all stages of user involvement in software development lifecycle (SDLC) process can contributes to the software usability. Although practitioners have agreed that user involvement in software development is very important but the extent of user involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
0
12
0
4
Order By: Relevance
“…It is better for users to be involved at all stages of the development process as noted by Majid et al (2010) and Noyes et al (1996) for better project results. The involvement of users in the development process should have an impact; users should be able to influence the decisions being made and not involved for the sake of it (Damodaran, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is better for users to be involved at all stages of the development process as noted by Majid et al (2010) and Noyes et al (1996) for better project results. The involvement of users in the development process should have an impact; users should be able to influence the decisions being made and not involved for the sake of it (Damodaran, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike authors that are specific about the stages users should be involved in the system development process, Majid et al (2010) and Noyes et al (1996) argue that users should be involved in all the different stages from the initial to the final phases of the process. Majid et al's (2010) research, where a survey on user involvement was carried out in the whole software development life cycle, concluded that involving users in all the phases of development is of significant importance and can in turn lead to a successful system.…”
Section: When To Involve Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…Selain itu, sistem yang digunakan juga harus di desain secara simple dan memiliki sistem navigasi yang mudah untuk dioperasikan (Hasnine dkk, 2015). HCI memiliki 6 aspek yang diperhatikan yaitu usability, understandability, learnability, operability, attractiveness, dan compliance (Majid, Noor & Wan, 2010). Untuk membangun sebuah sistem informasi yang digunakan untuk keperluan bisnis ataupun personal, HCI merupakan salah satu ilmu yang wajib untuk diperhatikan agar sistem yang dibangun dapat berjalan sesuai dengan kebutuhan user (Shiau, Yan dan Kuo, 2016).…”
Section: Dasar Teoriunclassified
“…1, it is evident that inception, elaboration, construction and transition are the four phases of software development life cycle (SDLC) and requirements forms the base for all the activities of SDLC phases. Requirements must be potential enough in terms of complete, consistent and unambiguous in order to develop a customer satisfied software during SDLC process [3], [4]. To possess enough potential to drive the above tasks, requirements must meet the highest quality.…”
Section: Introductionmentioning
confidence: 99%